Estimates of Combining Ability by Complete Diallel Crosses Analysis in Hexaploid Wheat Triticum aestivum L. - Najeeb Kakous Yousif; Manal Abdul Muttaleb AL-Hayali (Mesopotamia Journal of Agriculture)
Seven varieties of hexaploid wheat (Triticum aestivum L.) JAWAHIR-20, REYNA-27, ACHTAR, REBWAH-12 (group 7), REBWAH-12 (group 8), Ibaa 99 and Abo-Gharaib with their full dialed crosses were used in this study. Grains of parental varieties and their hybrids were planted at the college of Agricultural University of Mosul using randomized complete block design with four replications, during the growing season (2013-2014), depending on rain fed conditions. Genetical analysis was performed to determine the genetic systems for each of Plant height, Number of spikes, Biological yield, Grain yield, Weight of (100) grains and Number of grains per spike, also to estimate the general combining ability (G.C.A) and specific combining ability (S.C.A). F-test showed significant differences among the genotypes, both general and specific combining abilities for all studied traits. The ratio between the variance components of general combining ability and  specific combining ability was less than ore for all studied traits except for number of spikes, and (100) grains weight. Parental varieties distinguished with general combining ability for the some studied traits. The following hybrids showed high and desirable values for specific combining ability effects to the traits: (1×6) for biological yield and weight (100) grains, and (4×2) for number of spikes, weight (100) grains, and (3×7) for grain yield, and (4×6) for plant height, and (5×6) for plant height, and (6×7) grain yield, biological yield and weight (100) grains.